Estimation of breast implant volumes: error assessment of the subjective judgment method - Henseler, Helga; Hille-Betz, Ursula; Vogt, Peter M. (GMS German Plastic, Reconstructive and Aesthetic Surgery – Burn and Hand Surgery, 2016)
Background: The degree of error in subjective estimation of breast implant volume remains unknown. Methods: Nine silicone breast implants were used by 16 examiners for subjective, blinded, implant volume estimation. The figures on the stamps were taken as the true breast implant volumes for comparison. The examiners were divided into two groups of equal size: experienced examiners (consultant breast surgeons) and unexperienced examiners (trainees). Fourteen examiners repeated the tests after about 2 weeks.Results: In both groups of doctors, the implant volumes were underestimated by a mean ± standard deviation of 61.6 ± 58.1 cc (21.9% ± 20.1%) in the first test and 37.9 ± 59.1 cc (13.6% ± 20.7%) in the second test. The absolute deviation independent of volume overestimation or underestimation was 77.3 ± 36.9 cc (27.2% ± 12.8%) in the first test and 58.1 ± 41.3 cc (20.6% ± 14.6%) in the second test. In terms of absolute figures, the experienced examiners showed significantly better results than did the unexperienced examiners during the first test. The unexperienced examiners showed increasing deviations with increasing implant volumes. The degree of estimation error was lower in the second test.Conclusions: These blinded subjective estimations of breast implant volume exhibited limited accuracy and reproducibility. Estimation errors were quantified and increased with increasing implant volumes. Experienced examiners performed considerably better than unexperienced examiners, and results of the second test were better in both groups. The subjective volume estimations deviated from the true volumes by around 70 cc (underestimated by around 50 cc).Level of evidence: Level III